1971
DOI: 10.1136/bmj.2.5761.558
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Emptying of the Stomach with Metoclopramide

Abstract: SummaryThis paper evaluates the use of metoclopramide (MaxoIon) in emptying human stomach contents into the duodenum and beyond. A method of quantitative assessment of content by barium swallow radiography is used in the study, and the method is recommended as a diagnostic manoeuvre in patients presenting for emergency surgery in whom the stomach content is in doubt.Oral metoclopramide was found effective in emptying stomachs challenged by water load, and the intravenous route has been found effective in empty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1972
1972
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Metoclopramide has been shown to increase gastric emptying with equal efficiency whether given orally or intravenously, 16,23 indicating that the drug is fully absorbed. The effects that we have recorded in our study on ethanol levels support this view.…”
Section: Discussionmentioning
confidence: 99%
“…Metoclopramide has been shown to increase gastric emptying with equal efficiency whether given orally or intravenously, 16,23 indicating that the drug is fully absorbed. The effects that we have recorded in our study on ethanol levels support this view.…”
Section: Discussionmentioning
confidence: 99%
“…It accelerates gastric emptying (Jacoby and Brodie, 1967;Connell and George, 1969;Kreel, 1970; Howels, Khanam, Kreel, Seymour, Oliver, and Davies, 1971) and stimulates contraction of the small bowel (Tinker and Cox, 1969). These effects may be due to activation of intramural cholinergic motor mechanisms (Jacoby and Brodie, 1967;Eisner, 1968).…”
mentioning
confidence: 99%
“…Trauma can delay gastric emptying [16], and it has been shown that the severity of the trauma is a more important determinant of the residual gastric volume than the fasting time [17]. The more severe the pain, the greater is the degree of stomach paralysis [18].…”
Section: Discussionmentioning
confidence: 99%